Raccoons - Kissock, Heather (New York, NY : AV2 by Weigl, 2017)
Discover the amazing life cycles of American backyard animals in Little Backyard Animals. Told from the perspective of a child, each title follows a featured animals development from infancy to adulthood. Young readers will learn how animals grow through factual text told from a relatable perspective.
Keywords: Raccoons -- Juvenile literature; Raccoons